Perceptions and reality: Economic voting at the 2004 European Parliament elections - Tilley, J; Garry, J; Bold, T (Wiley Blackwell, 2008)
One of the most influential explanations of voting behaviour is based on economic factors: when the economy is doing well, voters reward the incumbent government and when the economy is doing badly, voters punish the incumbent. This reward-punishment model is thought to be particularly appropriate at second order contests such as European Parliament elections. Yet operationalising this economic voting model using citizens’ perceptions of economic performance may suffer from endogeneity problems if citizens’ perceptions are in fact a function of their party preferences rather than being a cause of their party preferences. Thus, this article models a ‘strict’ version of economic voting in which they purge citizens’ economic perceptions of partisan effects and only use as a predictor of voting that portion of citizens’ economic perceptions that is caused by the real world economy. Using data on voting at the 2004 European Parliament elections for 23 European Union electorates, the article finds some, but limited, evidence for economic voting that is dependent on both voter sophistication and clarity of responsibility for the economy within any country. First, only politically sophisticated voters’ subjective economic assessments are in fact grounded in economic reality. Second, the portion of subjective economic assessments that is a function of the real world economy is a significant predictor of voting only in single party government contexts where there can be a clear attribution of responsibility. For coalition government contexts, the article finds essentially no impact of the real economy via economic perceptions on vote choice, at least at European Parliament elections